2007
DOI: 10.2105/ajph.2005.082057
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Model Public Health Laws

Abstract: Model public health laws (public health laws or private policies publicly recommended by at least 1 organization for adoption by government bodies or by specified private entities) are promoted as exemplary. We assessed the information sponsors of model public health laws provide on the methods used in developing their models and on their models' adoption and effectiveness. Through a systematic search, we identified 107 model public health laws published from 1907 to 2004. As of our assessment in 2005, only 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…Nonetheless, public health policy making often is not informed by available evidence (3,4). Kingdon’s Multiple Streams Framework of how policy change happens defines the policy stream as the space where solutions compete for acceptance during decision making around an agreed-upon problem (5), such as cancer control.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, public health policy making often is not informed by available evidence (3,4). Kingdon’s Multiple Streams Framework of how policy change happens defines the policy stream as the space where solutions compete for acceptance during decision making around an agreed-upon problem (5), such as cancer control.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews such as the Guide to Community Preventive Services allow researchers and policy makers to identify evidence‐based policy 4 . Yet in a systematic review of 107 “model” public health laws (ie, public health or private policy publicly recommended by at least 1 organization for adoption by government bodies or by specified private entities), Hartsfield and colleagues found no model laws focusing on promotion of physical education 10 …”
mentioning
confidence: 99%
“…In their review of more than 100 model public health laws (i.e., a public health law or private policy that is publicly recommended by at least one organization for adoption by government bodies or by specified private entities) from 1907 to 2004, for example, Hartsfield, Moulton, and McKie (2007) found that sponsors provided information on these model laws' scientific basis and adoption in less than 10% of cases and no sponsor provided information on model effectiveness. A qualitative study by Elliott and Popay published in 2000 confirms this point.…”
Section: Political Casementioning
confidence: 99%